ON THE ALLEGED ”ROMAN ROAD FROM LOWER MOLDAVIA” - Ovidiu Tentea (Journal of Ancient History and Archaeology)
We shall analyse herein a few elements that do not support the existence of a road on the Barboși – Poiana - Brețcu route, as Pârvan assumed over one century ago. We shall discuss a few aspects referring to the site at Barboși, some finds in the fort at Brețcu and make a few notes on the diffusion of import goods on Siret river course.